A produção das desigualdades: análise da relação entre trabalho infantil e indicadores sociais - Silveira, Natércia Janine Dantas da (2014)
The International Labor Organization (OIT) estimates that there are around 118 million children subjected to child labor around the world. In Brazil, there are 3.5 million workers aged between 5 and 17. This exploitation practice constitutes a serious social problem, including of Public Health, since these workers are exposed to a wide range of risks, such as those related to health, physical integrity and even to life, which may cause them to become sick adults and/or interrupt their lives prematurely. Therefore, this research aims to investigate the relationship between the frequency of child labor in the age group of 10 to 13 years and some socio-economic indicators. It is a quantitative research in an ecological study whose levels of analysis are the Brazilian municipalities grouped in 161 regions, defined from socioeconomic criteria. The dependent variable of this study was the prevalence of child labor in the age group of 10 to 13 years. The independent variables were selected after a correlation between the 2010 Census of child labor in the age group of 10 to 13 years and secondary data had been conducted, adopting two main independent variables: funds from the Family Allowance Program (PBF) per 1,000 inhabitants and Funds from the Child Labor Eradication Program (PETI) per a thousand inhabitants. Initially, it was conducted a descriptive analysis of the variables of the study, then, a bivariate analysis, and the correlation matrix was built. At last, the Multiple Linear Regression stratified analysis was performed. The results of this survey indicate that public policies , like the Bolsa Familia Program Features per 1000 inhabitants and Resources Program for the Eradication of Child Labour to be allocated to municipalities with HDI < 0.697 represent a decrease in the rate of child labor ; These programs have the resources to be invested in municipalities with HDI > = 0.697 have no effect on the rate of child labor. Other adjustment variables showed significance, among these the municipal Human Development Index (IDH), years of schooling at 18 years of age, illiteracy at 15 years of age or more, employees without employment contract at 18 years of age and the Gini Index. It is understood that the child labor issue is complex. The problem is associated, although not restricted to, poverty, the social exclusion and inequality that exist in Brazil, but other factors of cultural and economic nature, as well as of organization of production, also account for its aggravation. Fighting child labor involves a wide intersectoral articulation, shared and integrated with several public policies, among them health, sports, culture, agriculture, labor and human rights, with a view to guaranteeing the integrality of the rights of children and adolescents in situation of labor and of their respective families